Weighting the resources: Determinant factors of poverty in housholds from Monclova, Aguascalientes, and Mexico City - Rojas-García, Georgina (Papeles de Población, 2021)
This paper aims to estimate the magnitude of poverty in three Mexican cities and to identify its determinants. Despite the number studies about poverty in our country, research on specific cities is rare, mainly due to limited information sources. In this paper, I propose an estimation of poverty based on the Mexican National Urban Employment Survey (Encuesta Nacional de Empleo Urbano-ENEU). Mexico City, Aguascalientes, and Monclova are chosen of case studies because of their contrasting economic experiences. The paper traces the trend of urban poverty in Mexico during the 1990s, as well as the magnitude of poverty in those three cities for 1993, 1996, and 2000, examining three periods: before, during, and after the peso devaluation crisis that began in december, 1994. Additionally, marshalling evidence reported by ethnographic observation of poor households’ resources, this study assesses the relative weight of those resources based on a series of logistic regression models. I then gauge and discuss the differential effect of the following factors that put families at risk of falling into poverty: city of residence, demographic characteristics of households, education, labor force, and housing.